Porous becomings anthropological engagements with Michel Serres - Bandak, Andreas; Knight, Daniel M. (Duke University Press, 2024)
"Porous Becomings brings anthropology into conversation with the late French philosopher Michel Serres (1930-2019). Serres championed an understanding of the human condition that transcended space, time, and episteme. Breaking free from disciplinary dogmas, Serres' reflections on science, culture, technology, art, and religion have proved foundational to scholars across the humanities. The editors note the long anthropological engagement with Bruno Latour, Gilles Deleuze, and Isabelle Stengers, work which disrupts conventional bounded thinking. They call for a similar conversation with Serres and gather anthropologists, including Elizabeth Povinelli and Michael Jackson, working in that idiom. The book concludes with a conversation between the editors and Jane Bennett, who has made significant use of Serres in her own work. Porous Becomings is intended to be more than simply the insertion of another French philosopher into the anthropological debate, instead providing critical insight into the theoretical and methodological apparatus of the discipline itself, allowing us to better confront a world in entangled polycrisis."
Keywords: Serres, Michel -- 1930-2019; Kultur; Wissenschaft; Technologie; Religion; Conditio humana; Kunst; Serres, Michel; Anthropology / Philosophy; Culture / Philosophy; Science / Philosophy; Anthropologie / Philosophie; SOCIAL SCIENCE / Anthropology / Cultural & Social; PHILOSOPHY / Movements / Critical Theory; Aufsatzsammlung